Active – Passive: On Preconceptions of Testing - Brzeziński, Krzysztof M. (Journal of Telecommunications and Information Technology, 2023)
In telecommunications and software engineering, testing is normally understood to be essentially active: a tester is said to stimulate, control, and enforce. Passive testing does not fit this paradigm and thus remains the niche research subject, which bears on the scope and depth of the obtained results. It is argued that such limited understanding of testing is one of its many community-bound preconceptions. It may be acceptable in the current engineering approach to testing, but can and should be challenged in order to converge on the core concepts of the proposed science of testing (“testology”). This methodological work aims at establishing that there are no fundamental reasons for admitting the dominant role of the active element in testing. To show this, external (also extratechnical) areas are consulted for insight, direct observations, and metaphors. The troublesome distinction between (passive) testing and monitoring, as well as unclear relations between testing and measurements, are also addressed.